Optimalisasi Peran Perawat dalam Melakukan Screening Palliative Care - Rohman, Asri Aprilia; Permana, Irfan; Febrianti, Isnaeni; Melia, Melia (Yayasan Inspirasi El Burhani, 2024)
Based on WHO data (2019), there are 40 billion people in the world who need palliative care, including those suffering from chronic diseases such as cardiovascular disease (38.5%), cancer (34%), chronic lung disease (10.3%), AIDS (5.7%), diabetes (4.6%), kidney failure, chronic liver disease, multiple sclerosis, Parkinson's and neurological diseases, rheumatoid arthritis, dementia, congenital disorders, and drug-resistant tuberculosis. Optimizing the role of nurses in palliative care screening is a crucial step for implementing effective nursing interventions. Appropriate screening allows early identification of patient needs, so that nurses can design and implement interventions that suit individual patient needs. The aim of this community service is to increase the knowledge and abilities of nurses in providing palliative nursing care to patients with chronic and terminal illnesses. The methods used to solve partner problems are community education and training. Community education is carried out by the service team by providing material about the basic concepts of palliative nursing, end of life, screening palliative care (SPC), palliative nursing care. The results of this Community Service activity show that there is an increase in nurses' knowledge about palliative nursing after following the training provided by the Community Service Team, as shown by the post test scores of the majority of participants having a good level of knowledge, 17 nurses (80.9%).